If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 4(1 + -3x) = 2x + -4(6x + 5) -2x + (1 * 4 + -3x * 4) = 2x + -4(6x + 5) -2x + (4 + -12x) = 2x + -4(6x + 5) Reorder the terms: 4 + -2x + -12x = 2x + -4(6x + 5) Combine like terms: -2x + -12x = -14x 4 + -14x = 2x + -4(6x + 5) Reorder the terms: 4 + -14x = 2x + -4(5 + 6x) 4 + -14x = 2x + (5 * -4 + 6x * -4) 4 + -14x = 2x + (-20 + -24x) Reorder the terms: 4 + -14x = -20 + 2x + -24x Combine like terms: 2x + -24x = -22x 4 + -14x = -20 + -22x Solving 4 + -14x = -20 + -22x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '22x' to each side of the equation. 4 + -14x + 22x = -20 + -22x + 22x Combine like terms: -14x + 22x = 8x 4 + 8x = -20 + -22x + 22x Combine like terms: -22x + 22x = 0 4 + 8x = -20 + 0 4 + 8x = -20 Add '-4' to each side of the equation. 4 + -4 + 8x = -20 + -4 Combine like terms: 4 + -4 = 0 0 + 8x = -20 + -4 8x = -20 + -4 Combine like terms: -20 + -4 = -24 8x = -24 Divide each side by '8'. x = -3 Simplifying x = -3
| 1-4n+3=4n-7n-2 | | 9(5b+4)= | | -(a+1)=7-a | | y+30=8 | | 0.3(x+100)+1.5=111 | | 36x-90-30x-60-3x-15=16x+24-6x+6-6+8x | | 10.19-3.3q+7.2q=2.8q-11.59 | | 3x+30=X-2 | | 3x+7x=4x-9 | | 4ab+4a= | | -6.5z+2.26=-17.74-7.5z | | -5w-(7z-6w)-2z= | | 12-m-9m=-20-12m | | x+8=1-6x | | -4w-5(-7x+4w)+6x= | | -3(x-5)-(2x+13)=-4(2x+2)+2(x-3)-2x-4x | | x+10=-y+10 | | -4(-3w-3z)-2(-6z-w)= | | 5x-2-3x=17+12x-23 | | 8f+9=21 | | 5n-n=0 | | -2(3h-1)=5(2h-3) | | g+9+7g=-11+9g | | 2a+4=5a-8 | | 26+8m=6-4(1-5m) | | 9-10v=-9v+13 | | 5(y+5)=y+37 | | -3[x+6]+5=-4 | | 4(5-w)=2(2w-3) | | 36=0.9y | | 0.04a+0.02(a-4)=0.3(0.1a-0.2) | | 13t+(-12)=12t+(-12t)+3.14 |